(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Describe knowledge of stroke prevention among hypertensive outpatients at Nghia Dan district medical center, Nghe An province in 2024. Method: A cross-sectional descriptive study was conducted on 132 hypertensive outpatients who met the selection criteria and answered the questionnaire. Results: Mean score of patients’ general knowledge was 7,32 ± 0,85 points/10 points, in which, 23.5% of the participants had good knowledge, 43.9% of them had average knowledge, and 32.6% of them had poor knowledge. Patients with higher education level, Kinh ethnic patients and patients living in urban areas had higher scores of knowledge of stroke prevention, the difference is statistically significant with p < 0.05. The duration of illness was positively related to the average level of stroke prevention knowledge (r = 0.571; p < 0.05) Conclusion: Hypertensive patients’ knowledge of stroke prevention was at an average level. Nurses should conduct education consultation to improve knowledge of stroke prevention for hypertensive patients, especially for patients of ethnic minorities, patients with low education levels and patients living in remote areas.